PENGEMBANGAN SUMBERDAYA MANUSIA BIDANG KEARSIPAN DI DINAS KEBUDAYAAN DAN PARIWISATA KALIMANTAN BARAT - Dewi E.01108015, Ayu Sartika (FISIP Universitas Tanjungpura, 2013)
Archive is an important aspect of administration, which the activity plays role as the center of documentation at every event of government office.Thus, archive management is required. Human resource development is one of factors to help strengthen archive management in particular government office. The focus of this research is to discuss the capacity building of archive staff of cultural and tourism office in the perspective of built in training (BIT) project, staff promotion, carrier development and quality control force. The subject of this study is the government office of culture and tourism in West Kalimantan, Indonesia, and the method is qualitative. This research reveals that the archive management of the office is generally low, andless number of functional staff in the archive division is one of the problems regarding the performance. Therefore, the study suggests that more staff is encouraged to participate in functional training of archive management. Besides, BIT is potential to enhance the capacity of archive staff. Regarding more trained staff, they should be placed directly to get involved to organize archive management and put to strengthen the archive system.Â Carrier promotion is also crucial to encourage particular employee who show significant achievement in managing archive. Then, quality control force is also potential to show the role of archive staff as the organization asset.Â Keyword: Human resource development, archive management.